Avaliacão da concordância entre o autorrelato da criança e do proxy na avaliação da qualidade de vida à saúde em pacientes com bronquiolite obliterante - Arend, Márcia Helena Rodrigues de Freitas (2018)
Introduction: Post-Infectious Obliterating Bronchiolitis is a chronic obstructive pulmonary disease that affects the distal airways. Pneumopathy is rare and severe, does not have a definite cause, numerous causes lead to the picture of a secondary insult. Subjective measures such as health-related quality of life (HRQoL) are being increasingly used to measure the impact of Bronchiolitis Obliterans on children's lives. Currently, there is a paucity of studies that have evaluated health-related quality of life in patients with Post-Infectious Bronchiolitis Obliterating. Objective: To assess the level of agreement in health-related quality of life (HRQoL) between children with Post Infectious Bronchiolitis Obliterans (PIBOPI) and their parent (so-called proxy). Methodology: Participants aged between 8-17, which had been previously diagnosed with PIBOPI, were regularly followed up at a pediatric pulmonology outpatient clinic. Parents or legal guardians (caregivers) of these patients were also recruited for they. A validated and age-appropriate version of the Pediatric Quality of Life Inventory 4.0 (PedsQL) was used for the assessment of HRQoL. Caregivers completed the corresponding proxy versions of the questionnaire. The correlation between self and proxy reports of HRQoL was determined by intra-class correlation coefficient (ICC), and dependent t-tests. Results: The majority of the participants were males (79.4%), and the average age was 11.8 years. Intra-class correlations between each of the PedsQL domains and the total score were all lower than 0.6, with a range between 0.267 (poor) and 0.530 (fair). When the means of each domain and the total score of the questionnaires were compared, caregivers were observed to score significantly lower HRQoL than children, with the exception of the social domain in which the difference was not significant. However, the differences in score exceeded the critical threshold difference of 4 points in all other domains. Conclusions: Proxys from patients with Post Infectious Bronchiolitis Obliterans tend to report lower quality of life scores than patients themselves.